A rotina de crianças de zero a dois anos na educação infantil e as especificidades infantis - Moura, Marianne da Cruz (2012)
In current upbringing production, children are often conceived as rightful subjects, and concrete and singular people, marked by specificities that schools must respect, mainly their personal wholeness, their care and attention needs, as well as their abilities to learn and produce culture. In the educational practices frame, routine is considered to have a definitive roll in time, space and activities structuring, as with actions and relations of subjects involved. In that perspective, this research aims to analyze routines of zero to two years old children in the upbringing context, relating to their childish specificities. Anchored in the qualitative approach, a Case Study was developed, according the procedures of daily routine observation and semi-structured interviews with six nursery teachers of CMEI Centro Municipal de Educação Infantil, Natal-RN, the research field. The data analysis was based in Speech Analysis principles. The teachers utterances regarding routine and it s roll in the frame revealed significances related to control/regulation of actions theirs and students aiming to streamline tasks; learning relative to routine itself, time and school practices. Thus, prospects of discipline and exercise of power of teachers over students surges, reducing their possibilities to participate. These conceptions reflect the daily routine of the kids and their teachers. By analyzing the methods of routine operation in the time/space/activities frame of CMEI, it was possible to perceive its homogenization of actions and rhythms, not only of the group s children, but the whole institution, which creates, many times, a controlling character that contains/prevents children s initiative. However, it was also possible to observe that in routine recesses, when it s relaxed, and other spaces, times and actions are provided, kids have the opportunity to experience and create different ways of action and relation with time, materials, other kids and teachers, being, as such, respected their specificities. We highlight the importance of reflections regarding routine in upbringing context, as to comprehend it s functions and the need for it s construction to take a multiple character that respects the plurality of situations and singularities of children as persons